IL-10 Has Differential Effects on the Innate and Adaptive Immune Systems of Septic Patients - Mazer, Monty (J Immunol, 2019)
Sepsis, a disease of divergent pro- and anti-inflammatory–mediated pathways, has a high prevalence of morbidity and mortality, yet an understanding of potential unifying mediators between these pathways that may improve clinical outcomes is largely unclear. IL-10 has classically been designated an immunosuppressive cytokine, although recent data suggest that under certain conditions IL-10 can be immune stimulatory. We sought to further investigate the effect of IL-10 on innate and adaptive immunity in an in vitro human observational cohort study in patients with sepsis via modulation of IL-10 on IFN-γ production by T cells and TNF-α production and HLA-DR expression by monocytes. These results were compared with critically ill nonseptic patients and healthy volunteers. ELISpot analysis was performed using PBMC fraction from patient whole-blood samples. Finally, to provide additional potential clinical relevance, we examined the effect of IL-10 on T cell IFN-γ production in an in vivo cecal ligation and puncture model of sepsis using C57 black/J6 female mice. We found that inhibition of IL-10 significantly increased both production of T cell IFN-γ and monocyte TNF-α, whereas addition of IL-10 increased T cell IFN-γ production but decreased monocyte production of TNF-α and HLA-DR expression. There was no significant effect of IL-10 on control cohorts. IL-10–treated septic mice demonstrated increased IFN-γ production in splenocytes. Thus, IL-10 demonstrates both pro- and anti-inflammatory effects in the septic microenvironment, which is likely cell and context dependent. Further elucidation of relevant signaling pathways may direct future therapeutic targets.